In practice: RECOVERY Trial - Horby, P; Peto, L; Landray, M (Springer, 2024)
The Randomised Evaluation of coronavirus disease 2019 (COVID-19) Therapy Trial (RECOVERY) has been the largest COVID-19 treatment study conducted. It provided compelling evidence on the safety and efficacy, or lack thereof, of a multitude of therapies postulated to be of benefit to COVID-19 patients. This chapter describes the background and environment that led to the protocol design, the key characteristics of the protocol, the operational elements facilitating speedy execution of the study, and the impact and subsequent international expansion of the study.